Bewässerungsgebiete und Bewässerungsprojekte in Südostitalien.: Begleitworte zu einer Karte - Rother, Klaus (ERDKUNDE, 1980)
A new map of irrigation areas is designed for the hygrically-disadvantaged areas of Apulia and Lucania on the basis of new source material and fieldwork carried out by the author. It shows that the area under irrigation remains small and near the coast. The changing principles of the water procurement policy and the increase in the demand for water after World War II are discussed, and modern irrigation schemes - largely limited to those of the coastal lowlands (Tavoliere, Metapontino) - are described in detail in the example of the Sinni Aqueduct